ANALYSIS OF THE MODELING APPLICATION’S TRENDS IN THE EDUCATIONAL PROCESS FOR THE PERIOD 2020 – 2023 - Taan, Ghazi Hussein (Journal of Tikrit University for Humanities, 2024)
The idea of ​​the current study is summarized in the reference review procedure of the directions of modeling process application in the educational process at the Arabic and foreign levels for the period (2020 - 2023). The study has followed the descriptive approach by presenting the modeling concept and the research fields that have addressed in various languages, in addition to identifying the most important models used in the educational process, based on the global database which are available on: (Google scholar, elibrary.ru, Scopus, …etc.). The study included (319), Arabic and foreign studies that dealt with restriction and numerical, qualitative and methodological classification during the time period from 2020 to 2023. The study has revealed the most important directions that used modeling as a research method. The study also showed the models set that were used in the educational process. It is hoped that analyzing directions will contribute to identifying the fields and departments in which modeling has been used to solve educational and scientific problems. The study has showed a set of results that evaluate this study, which could help researchers in the field of applying the modeling process as a research method.